63‐4: Invited Paper: New Optical Films for Next Generation AR Head Up Displays (HUDs). Issue 1 (29th May 2019) - Derlofske, John Van; Pankratz, Steve; Johnson, Matt; Franey, Eileen
Abstract : In an effort to improve safety by reducing driver distraction, vehicle manufacturers are migrating to Head Up Displays (HUDs) that incorporate augmented reality (AR), potentially into two or more visual planes. While much of the basic technology underlying AR HUDs is well known, widespread migration has been limited in large part by degraded image visibility through polarized sunglasses, visual artifacts (e.g. ghosting) caused by layered windshield safety glass, and the high operating temperatures within picture generation units (PGUs). Recent advances have led to new multilayer optical films that improve HUD image visibility, reduce visual artifacts, and decrease the thermal load at the PGU.